Issues in Teaching, Learning and Testing Speaking in a Second Language - Pawlak, Mirosław (Springer, 2016)
The volume constitutes a state-of-the-art account of issues related to teaching, learning and testing speaking in a second language. It brings together contributions by Polish and international scholars which seek to create links between theory, research and classroom practice, report the findings of studies investigating the impact of linguistic, cognitive and affective factors on the development and use of speaking skills, and provide concrete pedagogic proposals for instruction and assessment in this area. As such, the book will be of interest not only to second language acquisition theorists and researchers, but also to foreign language teachers willing to enhance the quality of speaking instruction in their classrooms.